2020
DOI: 10.1080/09540121.2020.1739216
|View full text |Cite
|
Sign up to set email alerts
|

The impact of common mental disorders among caregivers living with HIV on child cognitive development in Zimbabwe

Abstract: Common mental disorders (CMD) among caregivers living with HIV may affect their young children. The aim of this paper is to analyse the impact of maternal CMD among caregivers living with HIV on the cognitive functioning of their child.Data were collected at baseline and 12 months follow-up from mother-child dyads recruited as part of an ongoing trial among participants on the HIV-exposed infant register from 2 rural districts in Zimbabwe. Symptoms of CMD were assessed using the Shona Symptom Questionnaire (SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…This paper con rms presence of a signi cant relationship between maternal CMD and childhood malnutrition in Zimbabwe. There is a paucity of studies that assessed maternal CMD in Zimbabwe with a majority of studies mainly disease speci c for example CMDs among HIV infected mothers (30). We found a high burden of maternal CMDs in Zimbabwe in our study population (29.5%).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This paper con rms presence of a signi cant relationship between maternal CMD and childhood malnutrition in Zimbabwe. There is a paucity of studies that assessed maternal CMD in Zimbabwe with a majority of studies mainly disease speci c for example CMDs among HIV infected mothers (30). We found a high burden of maternal CMDs in Zimbabwe in our study population (29.5%).…”
Section: Discussionmentioning
confidence: 56%
“…Validation of the Shona Symptom Questionnaire established that using a cut-off of 5 a rmative responses from the 14 items is an accurate diagnosis of maternal CMD (29). We used the cut-off of 8 a rmative responses out of the 14 items as it is more commonly used in the literature reviewed (30,31)…”
Section: Maternal Cmdmentioning
confidence: 99%
“…Children were classified as scoring Average and above (summed [standardized] t‐ score: 85–155) and Below Average (summed [standardized] t‐ score: 49–84). The Mullen Scales of Early Learning have been found to have good psychometric properties, have been adapted for use in South Africa, and have been utilized widely within sub‐Saharan Africa (Boivin et al, 2019 ; Bornman et al, 2018 ; Mebrahtu et al, 2020 ; Milosavljevic et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Mebrahtu et al ( 3 ) focused on the potential risk and protective factors on children's cognitive development and found that increased maternal education levels protected against lower child developmental scores while increasing child age was a risk factor for lower developmental scores. Zhang Y. et al showed that perceived social support and trust could positively predict social wellbeing among youths affected by parental HIV/AIDS, implying trust appears to be the most proximate protective factor for social wellbeing.…”
mentioning
confidence: 99%